PENGARUH BRAND IMAGE DAN BRAND AWARENESS TERHADAP MINAT BELI PELANGGAN YANG DI MEDIASI OLEH BRAND TRUST PADA RICHEESE FACTORY DI KOTA BANDUNG - Amalia, Zainindakhoiri; Tania Adialita (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The intensity of fast food consumption in Indonesia is increasing. With the high level of consumption, the growth of the fast-food restaurant industry in Indonesia is also rapidly expanding to meet the needs of Indonesian consumers. However, this growth is not proportional to the decrease in the fast-food index of Richeese Factory on the Top Brand Index by 1.2%. This research is expected to provide benefits and information to Richeese Factory regarding purchasing interest and brand trust derived from brand image and brand awareness to support and enhance Richeese Factory's sales. The quantitative research method is obtained from survey responses using Likert scale questionnaires and analyzed using regression analysis with the assistance of SPSS 27. With the convenience sampling method, 160 respondents showed that brand image and awareness positively and significantly affect the purchase interest in Richeese Factory products. Furthermore, brand trust also successfully mediates the influence of brand image and brand awareness on the purchase interest in Richeese Factory products. The results of this research are also beneficial for decision-makers at PT Richeese Kuliner Indonesia regarding the design of relevant strategies or programs.